2018
DOI: 10.1007/s10798-018-9463-2
|View full text |Cite
|
Sign up to set email alerts
|

What is it called and how does it work: examining content validity and item design of teacher-made tests

Abstract: This article examines content validity in teacher made tests in elementary technology education-an interdisciplinary subject mandatory for all pupils in compulsory school in Sweden. The context of teacher-based assessments relies heavily on trust for teachers to cope with demands. Even though the system is challenged and preconditions for teachers' assessment practices are not always adequate to support instruction, much is unknown about teachers' assessment practices. In this explorative study, 30 teacher-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
8
0
4
Order By: Relevance
“…In the first place, they support the idea of reliability and validity being frequently disregarded by teachers when developing tests, as found by Badara (2016) in research aimed at determining the quality of Indonesian language teachermade tests at junior school level, and Quansah et al (2019) in a study at senior high schools in Ghana. Moreover, they are in agreement with Coniam's (2014) claim regarding worldwide English teachers' need to be guided in order to develop assessment and test design skills, and consistent with those of Hartell and Strimel (2018) who concluded that "different constructs and purposes demand different ways of assessment; therefore, the importance of assessment literate teachers is key" (p. 20).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the first place, they support the idea of reliability and validity being frequently disregarded by teachers when developing tests, as found by Badara (2016) in research aimed at determining the quality of Indonesian language teachermade tests at junior school level, and Quansah et al (2019) in a study at senior high schools in Ghana. Moreover, they are in agreement with Coniam's (2014) claim regarding worldwide English teachers' need to be guided in order to develop assessment and test design skills, and consistent with those of Hartell and Strimel (2018) who concluded that "different constructs and purposes demand different ways of assessment; therefore, the importance of assessment literate teachers is key" (p. 20).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, Hartell and Strimel (2018) examined content validity and item design of teacher-made tests in elementary technology education in Sweden. Their research suggests that there is a need for improvement since "items were unclear and often relied on questions that were easy to mark rather than items that best measured the prescribed abilities and core content stipulated in the Swedish technology curricula" (p. 18).…”
Section: Research Antecedentsmentioning
confidence: 99%
“…Prospective science teachers must be able to develop learning content or materials since it reflects independence in preparing learning sources. One of the ways to develop content is by integrating science content with knowledge gained from plentiful sources which are suitable for the characteristics of the field and scope (O'Byrne et al, 2015;Morrison, et al, 2015;Hartell and Strimel, 2018). Prospective science teachers are expected to create the knowledge integration on their own since it will result in a quality science learning at schools.…”
Section: Introductionmentioning
confidence: 99%
“…Přestože využívání teacher made testů lze považovat za jeden z efektivních nástrojů pro zajišťování zpětné vazby od žáků, je stále nutné myslet na skutečnost, že ne vždy disponují dostatečnou mírou reliablity a validity a zároveň že ne každý pedagog má dostatečné dovednosti k jejich správné evaluaci (srov. Mpofu, 2011;Hartell & Strimel, 2019). Učitelé dávají nejčastěji do popředí jednoduché úlohy na pamětní operace (Germ & Harms, 2008).…”
Section: Závěrunclassified